SEJARAH DAKWAH PANRITA KITTA : Islamisasi di Kabupaten Sinjai pada Abad XVII - Salsabila (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2025)
This study discusses the role and influence of Panrita Kitta in the process of Islamization in Sinjai in the 17th century. This type of research is library research using several historical, religious, and sociological approaches. The methods used in the study are heuristics, source criticism, interpretation, and historiography. The results of the study show the method of preaching, community responses, and the impact of Islamization on the development of local religion and culture. This study discusses more deeply the religious and cultural transformation of Sinjai in the 17th century. The pioneering Panrita of Islam in Sinjai in the 17th century focused on the reconstruction of the development of Islamic law. The influential Panrita were Puang Belle, Puatta Masabangnge, Tuanta Yusufu, To Maeppe Daeng Situncu, Syekh Ibrahim Rahmat, Wali Pute, To Palekke, Abdul Rahman Lamatti, Puang Janggo, and Puang Topekkong. From these findings, it is shown that the Islamization strategy implemented by Panrita Kitta prioritizes a cultural and Sufism approach, which is still relevant in the context of contemporary preaching. Unlike previous studies that only highlight historical aspects, this study also reveals the religious and cultural transformation of Sinjai in more depth, providing new insights into the study of Islamization in South Sulawesi, so that it is hoped that in the future it can focus on the relevance of Panrita Kitta's preaching with the current development of Islam, then can explore more in-depth historical sources, as well as comparisons with Islamization in other regions.